ProDab project: University extension in the thematic drugs of abuse – experience report - Maia Oliveira, Iris Cristina; do Carmo de Oliveira Citó, Maria; Lima Fernandes, Mariana; Ximenes dos Santos, Luciana Kelly; Caetano de Vasconcelos, Barbara; Florenço de Sousa, Francisca Cléa (Guará Journal, 2025)
The Drugs of Abuse Project (ProDab), affiliated with the Federal University of Ceará, develops preventive actions with students in Fortaleza on the topic of drugs of abuse. The actions developed in 2012 and 2013 included the training of school-based multipliers, the training of public school teachers, and the development of a drug use prevention manual. The activities developed by multipliers after the course demonstrate the assimilation of many concepts. Thus, ProDab's actions contributed to the school environment, connecting teaching and research, and enabling a transformative relationship between the university and society.
Keywords: Street Drugs; Adolescent